2003
DOI: 10.1002/j.1556-6678.2003.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Time in Later Life: Implications for Counseling

Abstract: Psychological time consists of cognitive constructs, images, and symbolic representations. It has different dimensions such as the experience of time, time perspective, attitudes and beliefs toward time, and the individual's behavior relating to time. Psychological time undergoes changes throughout the life span and is an integral part of the psychological developmental processes. In later life, it may be particularly dissonant with environmental rhythms and require re‐integration of the individual's past, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 54 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…The reminiscence function "Death Preparation", the way we use our past in order to achieve a calm and accepting attitude towards our own mortality, has been related to higher life satisfaction (Cappeliez Our study shows that a future orientation is significantly correlated with a higher positive affect. Caregivers should therefore be aware that giving older persons the chance to anticipate the future by encouraging them to make future plans based on realistic and feasible goals would give them a higher positive affect and an enhanced feeling of control over their lives (Shmotkin & Eyal, 2003;Heckhausen & Schulz, 1995;Fry, 1990). Prenda and Lachman (2001) also concluded that planning the future increases the level of satisfaction with life of older adults more than of younger persons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reminiscence function "Death Preparation", the way we use our past in order to achieve a calm and accepting attitude towards our own mortality, has been related to higher life satisfaction (Cappeliez Our study shows that a future orientation is significantly correlated with a higher positive affect. Caregivers should therefore be aware that giving older persons the chance to anticipate the future by encouraging them to make future plans based on realistic and feasible goals would give them a higher positive affect and an enhanced feeling of control over their lives (Shmotkin & Eyal, 2003;Heckhausen & Schulz, 1995;Fry, 1990). Prenda and Lachman (2001) also concluded that planning the future increases the level of satisfaction with life of older adults more than of younger persons.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers found that maintaining a future perspective is important for older people, if combined with other time orientations (Miller & Lieberman, 1965;Shifflett, 1987;Spence, 1968). Studies of the future TP showed that when the residents of an nursing home were given the opportunity to participate in planning future events, such as the film schedule or the visiting hours, they had a better sense of control over their lives and showed an improvement in their physical and mental health (Heckhausen & Schulz, 1995;Fry, 1990;Shmotkin & Eyal, 2003). As Marcoen, Grommen and Van Ranst (2006) pointed out, "a realistic future perspective would be an advantage for the adaptation and happiness of the elderly" (p. 139).…”
Section: Time Perspective Linked To Subjective Well-being In Later Lifementioning
confidence: 99%
“…However, SWB functions within past and future time coordinates as well (Shmotkin & Eyal, 2003). A rudimentary temporal frame was proposed by Cantril (1965) in his Self-Anchoring Scale, which consists of three ratings of satisfaction with the past (e.g., 5 years before), present, and future (e.g., 5 years ahead).…”
Section: Ingredients Of Narrative Swbmentioning
confidence: 99%
“…Among the diversity of existing psychological time theories and theories of future time as part of it (De Volder & Lens, 1982;Miller & Brickman, 2004;Ong & Bergeman, 2004;Shmotkin & Eyal, 2003;Golovakha & Kronik, 1984;Nuttin, 2004;Regush, 2003), most authors agree that one's life and motives are constructed in a certain "fi eld", the working space of which can be measured. In dangerous and stressful situations life perspective can decrease to the closest future goals and events, but during periods of calm refl ection it can be broaden to remote moments in the past and future and even go out of life time limits .…”
Section: Introductionmentioning
confidence: 99%